1997
DOI: 10.1099/00207713-47-3-607
|View full text |Cite
|
Sign up to set email alerts
|

Tsukamurella tyrosinosolvens sp. nov.

Abstract: Chemotaxonomic and 16S ribosomal DNA sequence analyses of four bacterial isolates from blood cultures from patients with cardiac pacemaker implants and sputa of patients with chronic lung infections clearly demonstrated that these bacteria belong to the genus Tsukamurella. DNA-DNA hybridization data, as well as the physiological characteristics of the isolates, indicate that they are closely related and belong to a single species that differs from previously described members of the genus Tsukamurella. The nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
35
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 6 publications
7
35
1
1
Order By: Relevance
“…With few discrepancies, our study of 15 strains of Tsukamurella generally showed good agreement between our phenotypic data and those reported by Yassin et al for T. paurometabola, T. inchonensis, T. pulmonis, and T. tyrosinosolvens (34)(35)(36). Testing for sugar utilization with the API 50 CH system showed excellent correlation with published data based on tests with conventional biochemicals.…”
Section: G Aurantiaca Was Renamed Rhodococcus Aurantiacus By Tsupporting
confidence: 79%
See 2 more Smart Citations
“…With few discrepancies, our study of 15 strains of Tsukamurella generally showed good agreement between our phenotypic data and those reported by Yassin et al for T. paurometabola, T. inchonensis, T. pulmonis, and T. tyrosinosolvens (34)(35)(36). Testing for sugar utilization with the API 50 CH system showed excellent correlation with published data based on tests with conventional biochemicals.…”
Section: G Aurantiaca Was Renamed Rhodococcus Aurantiacus By Tsupporting
confidence: 79%
“…Testing for sugar utilization with the API 50 CH system showed excellent correlation with published data based on tests with conventional biochemicals. However, with degradation agars, we found inconsistencies among different studies and with our results (2,24,(34)(35)(36). Moreover, in our study we found discrepancies between different commercial systems.…”
Section: G Aurantiaca Was Renamed Rhodococcus Aurantiacus By Tcontrasting
confidence: 56%
See 1 more Smart Citation
“…Asymmetrical daughter cells were generated from the fragmentation process of the transverse septa at one pole of each parental cell during growth (Fig. 2b, d), which was also in congruence with observations reported in previous studies (Yassin et al, 1996(Yassin et al, , 1997Teng et al, 2015).…”
supporting
confidence: 81%
“…Specifically, upon review of a Gram stain of the blood isolate, the differential was expanded to include mycobacterial pathogens and other aerobic actinomycoses, as well as Tsukamurella spp., in part due to the clinical picture and overlapping laboratory findings (11). Three days later, the patient developed acute renal insufficiency, due to the TMP-SMZ, and was rehospitalized for further management of his renal disease.…”
mentioning
confidence: 99%